The Expression of Leptin, Estrogen Receptors, and Vitellogenin mRNAs in Migrating Female Chum Salmon, Oncorhynchus keta The Effects of Hypo-osmotic Environmental Changes - Choi, Young Jae (Asian-Australasian journal of animal sciences, 2014)
Leptin plays an important role in energy homeostasis and reproductive function in fish, especially in reproduction. Migrating fish, such as salmonoids, are affected by external environmental factors, and salinity changes are a particularly important influence on spawning migrations. The aim of this study was to test whether changes in salinity affect the expression of leptin, estrogen receptors (ERs), and vitellogenin (VTG) in chum salmon (Oncorhynchus keta). The expression and activity of leptin, the expression of ERs and VTG, and the levels of estradiol-17β and cortisol increased after the fish were transferred to FW, demonstrating that changes in salinity stimulate the HPG axis in migrating female chum salmon. These findings reveal details about the role of elevated leptin levels and sex steroid hormones in stimulating sexual maturation and reproduction in response to salinity changes in chum salmon